How is The Coronavirus Outbreak Affecting The Daily Lives of University Students? - Dita Fahrun Nisa; Nuzulul Kusuma Putri (Universitas Airlangga, 2020)
Introduction: Covid19 disease is rapidly becoming a health problem in the world and has changed many aspects of human life. Many schools, including universities worldwide, have adjusted their way of the teaching method. While new online learning technologies have disrupted the sociocultural environment in higher education, there is a high possibility that students also faced a turbulent time. This study analyzed how the coronavirus outbreak affects the daily lives of university students. Method: This study used a cross-sectional study design which was conducted a month after the learning from home policy was implemented in Indonesia. We surveyed second and third-year university students about their experiences during this difficult time. There are 255 students of Public Health Bachelor Program responded to the survey. We asked what emotion they dominantly feel during the study at home period and how this pandemic changes their daily life. Their responses were analyzed using qualitative content analysis. Result and Discussion: The results showed that most students felt happy (41.51%) and the rest felt sad (34.38%) while studying at home. The other feelings are fear as much as 15.81%, surprise 7.91%, and anger 0.39%. We identified seven impacts of pandemic on the student's life. Four consequences related to the school closures, while three consequences related to the students development as human being. Conclusion: The study at home policy applies during the Covid19 pandemic has affected the lives of students both in their roles as students, adult and children in the family.